Titanium-35niobium alloy as a potential material for biomedical implants: in vitro study - Andrade, Dennia Perez de[UNESP]; Vasconcellos, Luana Marotta Reis de[UNESP]; Carvalho, Isabel Chaves Silva [UNESP]; Forte, Lilibeth Ferraz de Brito Penna [UNESP]; Souza Santos, Evelyn Luzia de [UNESP]; Prado, Renata Falchete do [UNESP]; Santos, Dalcy Roberto dos; Cairo, Carlos Alberto Alves; Carvalho, Yasmin Rodarte [UNESP] (Elsevier B. V., 2015)
Research on new titanium alloys and different surface topographies aims to improve osseointegration. The objective of this study is to analyze the behavior of osteogenic cells cultivated on porous and dense samples of titanium-niobium alloys, and to compare them with the behavior of such type of cells on commercial pure titanium. Samples prepared using powder metallurgy were characterized using scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), X-ray diffraction (XRD), and metallographic and profilometer analyses. Osteogenic cells from newborn rat calvaria were plated over different groups: dense or porous samples composed of Ti or Ti-35niobium (Nb). Cell adhesion, cell proliferation, MTT assay, cell morphology, protein total content, alkaline phosphatase activity, and mineralization nodules were assessed. Results from XRD and EDS analysis confirmed the presence of Ti and Nb in the test alloy. Metallographic analysis revealed interconnected pores, with pore size ranging from 138 to 150μm. The profilometer analysis detected the greatest rugosity within the dense alloy samples. In vitro tests revealed similar biocompatibility between Ti-35Nb and Ti; furthermore, it was possible to verify that the association of porous surface topography and the Ti-35Nb alloy positively influenced mineralized matrix formation. We propose that the Ti-35Nb alloy with porous topography constitutes a biocompatible material with great potential for use in biomedical implants.
Keywords: Biocompatibility; Implants; Osteogenesis; Porous surfaces; Titanium niobium alloy